2021
DOI: 10.1088/2053-1591/ac24f8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone-plate materials on the healing process of fractured tibia bone under time-varying conditions: a finite element analysis

Abstract: Stress shielding is known to cause bone refracture or cause low healing rate in fractured bones. The numerical study of bone healing process of a transverse fractured tibia was conducted in this research to reduce the stress shielding. The stress and strain on the callus were evaluated when bone plates of different metallic and non-metallic biomaterials were used. Time varying material properties of the callus were applied, and loading conditions were coupled with material properties of the callus. The strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Kumar et al [6] also reported in their study on the application of PEEK for spine application that PEEK is a highly suitable material and alternative to titanium alloy. ese results are augmented by research conducted by Tan et al [7].…”
Section: Introductionmentioning
confidence: 86%
“…Kumar et al [6] also reported in their study on the application of PEEK for spine application that PEEK is a highly suitable material and alternative to titanium alloy. ese results are augmented by research conducted by Tan et al [7].…”
Section: Introductionmentioning
confidence: 86%
“…In addition, the in vivo evaluation revealed that the newly formed bone volume of the ternary composite was higher than that using pure PEEK. Moreover, Tan et al [ 126 ] showed that PEEK/nano-HA/short carbon fiber bioactive composite provides the most suitable implant for bone plating application for tibia. Furthermore, Zhou and Yang [ 127 ] used carbon/PEEK composite plates and demonstrated that these lower-stiffness bone plates had reduced stress shielding at the fracture site.…”
Section: Peek Bioactivitymentioning
confidence: 99%
“…Finite element analysis (FEA) is an effective tool to reveal biomechanics ( Kaku et al, 2004 ) and has been widely applied to investigate the biomechanical behavior of spine and tibia bone with good agreement with experimental measurements ( Dalstra et al, 1995 ; Anderson et al, 2008 ; Anderson et al, 2010 ). Tan et al conducted numerical study of bone healing process of a transverse fractured tibia ( Tan et al, 2021 ). Kosalishkwaran et al applied this technique to the spine, proposing an innovative method for calculating RoM ( Kosalishkwaran et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%